Computational analysis of magnetohydrodynamic effects on biodiesel flow rate - Tatun Hayatun Nufus; Candra Damis Widiawati; Ahmad Indra Siswantara; Gun Gun Ramdlan Gunadi; Dianta Mustofa Kamal; Asep Apriana; Dela siska; Bayu Prasetio; Irfan Hermansyah Saputra (Politeknik Negeri Lhokseumawe, 2023)
The purpose of this research is to determine the velocity characteristics of fluid (fuel) flow in a pipe surrounded by a minimal magnetic (electromagnetic) field strength by using computational fluid dynamics simulations. For a more detailed discussion, Magnetohydrodynamics (MHD) theory is used, which is a branch of science that studies fluid flow that can conduct electric current due to the influence of a magnetic (electromagnet) field. The fuel used is B0, B10, B20 and B30. The magnitude of the electromagnetic field used is 0.15 Tesla. the result is that the flow rate of B0 fuel has decreased by 0.623%. B10 fell to 0.41%. The B20 was down 0.618% and the B30 was down 0.648%. Thus the magnetic field strength of 0.15 Tesla is able to change the speed of the fuel flow even if only slightly. This information is needed as a basis for the development that the magnetic field is able to change the value of the flow velocity, this will provide information related to improving the quality of combustion and fuel savings in the future.